EXTRATERRITORIAL JURISDICTION IN INTERNATIONAL LAW: A CASE STUDY OF DUE DILIGENCE IN THE EUROPEAN UNION DEFORESTATION-FREE REGULATION - Maranatha Lisatyaningrum Hainekam Fobia; Najwa Yorri Nordyaningrum (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The development of lifestyles and the complexity of human problems have led to changes in the concepts of sovereignty and national boundaries. One such complexity is environmental issues, the implications of which are not limited to one or a few countries but to the entire global community. Therefore, regulations aimed at environmental sustainability and preservation have become a primary objective of transnational activities. Deforestation is an international concern that requires serious attention. This spirit is manifested by the European Union in the European Union Deforestation-Free Regulation, which ensures that export products to the EU market are not made from materials derived from or through deforestation. This paper describes how the EUDR uses extraterritorial jurisdiction to strengthen a green economic climate, but at the same time, opens up weaknesses in sovereignty for developing countries that are exporters. This paper uses the theory of state sovereignty and the fundamental principles of international contract law as references. The research method used is a normative research method with a conceptual approach and a legislative approach.